A quantitative report on the present strategies of Graphical authentication - Dias, Norman; Reeja, SR (International Journal of Computer Sciences and Engineering, 2025)
The foremost common authentication strategy is to use alphanumeric usernames and passwords. This strategy has been appeared to posses critical disadvantages. Clients prefer to choose passwords which are effectively speculated. At the same time, if the password is difficult to figure, then at that point its obviously difficult to keep in mind. To solve this issue a few analyst have created verification strategy’s that utilizes images as passwords. This paper examines the qualities of the existing graphical passwords methodologies and we try to answer a question “whether a graphical password more secure to a text based password